MUTAGENESIS INDUCIDA EN PASTO SABOYA (Panicum maximum Jacq.) CON ETIL-METANOSULFONATO E INCIDENCIA DE SALIVAZO (Mahanarva andígena) Jacobi (Homóptera, Cercopidae), BAJO CONDICIONES DE INVERNADERO - Alvarado Álvarez, Bolívar Augusto (2022)
The savoy is an economically important grass that is attacked by insect pests such as the spittlebug, where an alternative is the induction of mutations using chemical substances such as ethyl-methanesulfonate (EMS) and the individual selection of plants with forage potential. In this perspective, a study was carried out with the objective: "Determine the incidence of Salivazo in Savoy grass by induced mutagenesis of ethyl-meta sulfonate, under greenhouse conditions". A completely randomized design of 9 treatments with five repetitions was used, in a factorial arrangement A x B +1. Factor A: seed impregnation times: 24 and 48 hours. Factor B: EMS concentrations: 0.25%, 0.50%, 0.75% and 1.00%, in addition to the control. The experimental units were 20 plants, which were evaluated at different times. The results made it possible to determine which morphological characteristics of savoy grass have a differentiated behavior in response to EMS impregnation, however, they are all correlated (p<0.05). The impregnation time had no effect on the agronomic behavior. The optimal concentration of EMS is 0.48. An increase in EMS concentration of 0.1% reduces the number of nymphs, by 2 nymphs/plant. The concentrations of 0.75% and 1.00%, regardless of the impregnation times, were effective in reducing the number of nymphs. The population of spittlebug nymphs tends to increase in the control plants, deducing that the pest goes through the different stages and that the reduction of nymphs is due to the effect of EMS